Analysis of Platelet Indices and Proteinuria in Primary Hypertensive Patients - Deny Suryana; Yuyun Widaningsih; Fitriani Mangarengi; Darwati Muhadi (Indonesian Association of Clinical Pathologist and Medical laboratory, 2022)
Hypertension is a silent killer that causes premature death, an estimated 9.4 million people die each year due to hypertension and its complications. Primary hypertension promotes endothelial damage-causing platelet release reaction. Without treatment, it may cause renal damage, which leads to proteinuria. This study aimed to analyze the relationship of the platelet indices (PLT, PDW, PCT, MPV) in predicting proteinuria among patients with primary hypertension based on its stage. A retrospective study using medical records of patients diagnosed with primary hypertension by clinicians at Dr. Wahidin Sudirohusodo Hospital from January-December 2019. Complete Blood Count (CBC) using the flow cytometry and routine urine test with urine analyzer were performed. The statistical test used in this study were the independent T-test, Chi-Square test, and oneway ANOVA test. Receiver Operating Characteristics (ROC) were used to determine the cut-off. The sample consisted of 78 patients. Mean Platelet Volume (MPV) was significantly higher in proteinuria patients and stage two hypertension with p<0.001. There was a significant relationship between stage two hypertension and proteinuria with p=0.018. ROC analysis showed MPV Area Under the Curve (AUC) of 0.774 with p<0.001, which indicated that MPV can be used as a predictor of proteinuria with a cut-off point of 8.55. MPV increases on the platelet indices, proteinuria with stage 2 hypertension are caused by damage to glomerular endothelium, which leads to platelet activation characterized by degranulation, swelling, and increases in platelet mass and volume. There was a relationship between an increase of MPV and proteinuria in patients with stage 2 hypertension.